C10 Description Of The Breathing Phenotype In Two Mouse Models For Huntington's Disease. (17th September 2014) - Schnell, C; Iarova, P; Brooks, SP; Kidd, E; Ford, W; Ricardi, D; Kemp, PJ; Busse, M
Abstract : Aspiration pneumoniais a major cause of death in people with Huntington's disease (HD). Furthermore, breathing irregularities and impaired swallowing in mid and late-stage HD are frequent clinical observations. These observations may berelated to impaired brain stem control of breathing and swallowing. Irregularbreathing patterns could also arise as a compensatory mechanism for decreased blood O2 and increased CO2 levels in the blood due to primary weakness of respiratory muscles or impaired O2 uptake in the lungs. In order to develop clinical therapies for people with HD affected by breathing and swallowing difficulties, it is necessary to understand the underlying cause for this problems. An animal model would be an invaluable tool for the investigation of the pathophysiological condition leading to breathing and swallowing problems observed in people with HD. The aim of this study is to identify and characterise an animal model for HD that share some of the pathological features with respect to breathing and swallowing. In our study we will monitor the breathing pattern of Detloff HdhQ50 and HdhQ250 mice employing whole-body plethysmography on a monthly basis to test for the occurrence of breathing disturbances during disease progression. We also plan to analyse blood samples, respiratory muscles, and lung tissue to see if the breathing problems are caused by disturbances in these tissues and not by impaired brain stem control of breathing.